If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = 2 + 2s Solving 14 = 2 + 2s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2s' to each side of the equation. 14 + -2s = 2 + 2s + -2s Combine like terms: 2s + -2s = 0 14 + -2s = 2 + 0 14 + -2s = 2 Add '-14' to each side of the equation. 14 + -14 + -2s = 2 + -14 Combine like terms: 14 + -14 = 0 0 + -2s = 2 + -14 -2s = 2 + -14 Combine like terms: 2 + -14 = -12 -2s = -12 Divide each side by '-2'. s = 6 Simplifying s = 6
| 3x-11=x+21 | | 4+4b=34.4 | | 24=6+7x-5x | | 14x(5-6)= | | 2(y+1)=y-4 | | 2+6s=26 | | 9y-13y=-10-14 | | 19-12a=79 | | x^4-x^2-14x+54=0 | | 93.3=13b-10.7 | | 3x+5+4x=5 | | 4a-1=-37 | | g(0)=3x^2-2x | | 3+4x-18= | | 2-5x=3x-14 | | -5(x-4)=0 | | -216+125x^3=0 | | x+x+1+x+2=90 | | 5(r-5)=2(r-4)-4 | | 3a-19=-49 | | 2(x-3)=34 | | 4x-23=3x-5 | | 6x+9-5x=12 | | 42a^4+60a^3=0 | | 5z+7=6(z-2)-4(2z-3) | | -39=6+5t | | 25x+5(x+5)+10(x-9)=3,115 | | 3(x)=18 | | (5x^4)(25x^2)= | | x+(x+2)+(x+4)=-17 | | I-4I= | | 2x-5=-4x-2 |